2021
DOI: 10.3390/ijms22168628
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Application Modifies Antioxidant Defense and Induces Endoreplication in Maize Seeds Exposed to Chilling Stress

Abstract: The aim of the study was to demonstrate the biostimulating effect of exogenous melatonin (MEL) applied to seeds via hydroconditioning. It was indicated that only well-chosen application technique and MEL dose guarantees success concerning seed germination and young seedlings growth under stress conditions. For maize seed, 50 μM of MEL appeared to be the optimal dose. It improved seed germination and embryonic axes growth especially during chilling stress (5 °C/14 days) and during regeneration after its subside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 82 publications
(112 reference statements)
1
15
0
Order By: Relevance
“…However, treatment with 200 µM MT under high-temperature conditions significantly enhanced the germination rate and potential, seed radicle growth, and fresh weight. These findings align well with prior research, which showed that an appropriate concentration of MT can bolster germination in the seed of rice, corn, wheat, and other seeds under stressful conditions, and stimulate radicle lengthening ( Kołodziejczyk, Kaźmierczak & Posmyk, 2021 ; Lei et al, 2021 ; Yu et al, 2022 ). In this study, soaking buckwheat seeds with MT could alleviate the inhibition effect of high temperature on seed germination.…”
Section: Discussionsupporting
confidence: 91%
“…However, treatment with 200 µM MT under high-temperature conditions significantly enhanced the germination rate and potential, seed radicle growth, and fresh weight. These findings align well with prior research, which showed that an appropriate concentration of MT can bolster germination in the seed of rice, corn, wheat, and other seeds under stressful conditions, and stimulate radicle lengthening ( Kołodziejczyk, Kaźmierczak & Posmyk, 2021 ; Lei et al, 2021 ; Yu et al, 2022 ). In this study, soaking buckwheat seeds with MT could alleviate the inhibition effect of high temperature on seed germination.…”
Section: Discussionsupporting
confidence: 91%
“…In a study performed on Pistacia vera (L.) grown under cold stress, application of melatonin caused a significant decrease in the expression of oxidative stress biomarkers, with a subsequent decrease in sugar, proline, and GABA content [140]. Melatonin treatment enhances seed germination and prevents protein and lipid oxidation in embryonic cells of Capsicum annum and Zea mays, besides causing an increase in the antioxidant levels [141,142]. Turk and Genisel reported that application of melatonin in maize plays an important role in improving plant growth attributes and in protecting plants from oxidative damage via reduction in the ROS levels [143].…”
Section: Melatonin Under Low Temperature Stressmentioning
confidence: 99%
“…Jasmonic acid (JA) has been used as a priming agent to treat tomato seeds, enhancing the seedling ability to withstand nematode attacks (Bali et al 2020 ). Priming with brassinosteroids (BRs) significantly enhanced tolerance to heavy metal toxicity (Basit et al 2021 , 2022 ), and drought (Huang et al 2020 ), whereas the use of melatonin contributed to improved cold tolerance (Cao et al 2019 ; Kołodziejczyk et al 2021 ). Due to the complexity of phytohormone metabolism and regulatory networks, the selection of suitable conditions and effective molecules for hormopriming depends on a deeper knowledge of several key molecular players and the way they could contribute to boosting germination (Bryksova et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%